1994
DOI: 10.1007/bf00417688
|View full text |Cite
|
Sign up to set email alerts
|

Aldose reductase inhibition, nerve perfusion, oxygenation and function in streptozotocin-diabetic rats: Dose-response considerations and independence from a myo-inositol mechanism

Abstract: We examined the effects of aldose reductase inhibition on nerve biochemistry and function, blood flow and endoneurial oxygenation in experimental diabetes mellitus. After 1 month untreated diabetes in rats, treatment with the novel sulphonylnitromethane aldose reductase inhibitor, ZENECA ZD5522, prevented a progressive increase in sciatic nerve resistance to hypoxic conduction failure (p < 0.05). Motor conduction velocity deficits after 4 months untreated diabetes were rapidly returned to normal within 12 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
62
1

Year Published

1994
1994
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 114 publications
(76 citation statements)
references
References 51 publications
13
62
1
Order By: Relevance
“…As has been previously reported, we demonstrate that treating streptozotocin-induced diabetic rats with sorbinil or aminoguanidine significantly improves the reduction in EBF and slowing of MNCV [3][4][5][6][7][8][9][10][11][12][24][25][26][27][28]. In sorbinil treated diabetic rats EBF and MNCV remained suppressed by 15 and 18%, respectively compared to controls, whereas in aminoguanidine treated rats EBF and MNCV, compared to controls, was decreased by 6 and 16%, respectively.…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…As has been previously reported, we demonstrate that treating streptozotocin-induced diabetic rats with sorbinil or aminoguanidine significantly improves the reduction in EBF and slowing of MNCV [3][4][5][6][7][8][9][10][11][12][24][25][26][27][28]. In sorbinil treated diabetic rats EBF and MNCV remained suppressed by 15 and 18%, respectively compared to controls, whereas in aminoguanidine treated rats EBF and MNCV, compared to controls, was decreased by 6 and 16%, respectively.…”
Section: Discussionsupporting
confidence: 71%
“…We have previously shown that endothelialdependent vascular relaxation of arterioles that provide circulation to the region of the sciatic nerve is impaired by diabetes [35,36]. In the present study we sought to determine the effect treatment of diabetic rats with sorbinil, an aldose reductase inhibitor, aminoguanidine, an inhibitor of nonenzymatic glycation, or myoinositol supplementation has on EBF, MNCV as well as vascular relaxation of arterioles that provide circulation to the region of the sciatic nerve.As has been previously reported, we demonstrate that treating streptozotocin-induced diabetic rats with sorbinil or aminoguanidine significantly improves the reduction in EBF and slowing of MNCV [3][4][5][6][7][8][9][10][11][12][24][25][26][27][28]. In sorbinil treated diabetic rats EBF and MNCV remained suppressed by 15 and 18%, respectively compared to controls, whereas in aminoguanidine treated rats EBF and MNCV, compared to controls, was decreased by 6 and 16%, respectively.…”
supporting
confidence: 71%
See 3 more Smart Citations